Iron Homeostasis and Hepcidin Concentration in Patients With Acromegaly - Krygier, Aleksandra; Szczepanek-Parulska, Ewelina; Cieślewicz, Maja; Wrotkowska, Elżbieta; Chanaj-Kaczmarek, Justyna; Ruchała, Marek (Frontiers in Endocrinology, 2022)
Hepcidin is a protein responsible for maintaining iron (Fe) homeostasis. Data regarding the role of hepcidin in the pathomechanism of Fe balance disturbances associated with acromegaly (AG) are scarce. The aim of the study was to assess the impact of alterations in complete blood count parameters, Fe homeostasis, gonadal status and GH/IGF-1 on the level of hepcidin in AG patients. The study evaluated the differences in hepcidin concentration and iron homeostasis between patients newly diagnosed with AG in comparison to healthy control subjects (CS). We prospectively enrolled 25 adult patients newly diagnosed with AG and 25 healthy volunteers who served as CS. The level of hepcidin was measured using the Hepcidin 25 (bioactive) hs ELISA, which is a highly sensitive enzyme immunoassay for the quantitative in vitro diagnostic measurement (DRG Instruments GmbH, Germany). The median of hepcidin concentration in the serum of patients with AG was significantly lower 9.8 (6.2-18.2) ng/ml as compared to CS 21.3 (14.3-34.0) ng/ml (p=0.003). In the AG group, a statistically significant negative correlation between hepcidin and IGF-1 (rho= -0.441) was observed. Our study demonstrated a decreased hepcidin level in AG patients in comparison to CS what may have a potentially protective effect against anaemia through an increased bioavailability of Fe. Additionally, GH may have a positive direct or indirect effect on erythropoiesis. Further studies on larger patient groups are necessary in order to clarify the exact role of hepcidin in the regulation of erythropoiesis in the excess of GH/IGF-1.